A Study on Digital Game Addictions of Adolescents in the Covid-19 Pandemic - Vahit Ciris; Turan Baskonus; Tezcan Kartal; Adem Tasdemir (Journal of Education in Science, Environment and Health)
The concept of digital game addiction has become an important issue that needs to be studied, depending on the increase in the time spent on the internet today, where technology and internet usage times are increasing rapidly. In this context, this study aimed to understand the antecedents of high school students’ online game addiction risks. The survey method was used in the study. Within the scope of the research, 559 high school students randomly selected from this population formed the sample of the study. The “Game Addiction Scale for Adolescents,” adapted into Turkish by Ilgaz (2015), was used as a data collection tool in the study. The results showed that digital game addictions of high school students were formed at the highest level in the dimensions of mood modifications, tolerance, and salience, respectively. The lowest averages were in the withdrawal and conflict dimensions. These findings show that high school students experience many emotional states in the game at a high level. Besides, while digital game addiction of male students was higher, it was determined that games played via computer caused more digital addiction. While digital game addictions of high school students do not change according to their grade level and academic achievement, their digital game addictions change according to family income level, playing time, and parental education level.